A common‐value auction with state‐dependent participation. Issue 2 (25th May 2022) - Lauermann, Stephan; Wolinsky, Asher
Abstract : This paper analyzes a common‐value, first‐price auction with state‐dependent participation. The number of bidders, which is unobservable to them, depends on the true value. For participation patterns with many bidders in each state, the bidding equilibrium may be of a "pooling" type—with high probability, the winning bid is the same across states and is below the ex ante expected value—or of a "partially revealing" type—with no significant atoms in the winning bid distribution and an expected winning bid increasing in the true value. Which of these forms will arise is determined by the likelihood ratio at the top of the signal distribution and the participation across states. We fully characterize this relation and show how the participation pattern determines the extent of information aggregation by the price.